RAYLEIGH-BENARD CONVECTION STUDY IN A CAVITY FOR A SHEAR THINNING FLUID - Ali Benyahia, B.; Ait Messouadene, N. (Journal of Fundamental and Applied Sciences, 2021)
Rayleigh-Bénard's convection is a classic problem of heat transfer. Since the 1900s, studies for Newtonian fluids have been widely developed in this field and phenomena well understood. On the other hand, the complexity of non-Newtonian behavior makes the number of studies much lower. Among the non-Newtonian behavior, the shear-thinning fluid studies are even rarer. This work focuses on a numerical study of natural convection for a non-Newtonian fluid shear thinning, in the Rayleigh-Bénard configuration. The shear thinning behavior is described by the Carreau-Yasuda model. The convective flow considered is confined in a cavity which is subjected to a vertical temperature gradient, heated from below and cooled from above. The transport equations are discretized by the finite volume method and are solved numerically using a CFD code: "Ansys Fluent".The influence of the control parameters on the flow and heat transfer such as the Rayleigh number, the aspect ratio, , the Prandtl numbers, , the power index and the time constant , are studied.